Experiences of the Medication Use Process by People with Intellectual Disabilities. What a Pharmacist Should Know! - Henman, Martin (My University, 2021)
There is a scarcity of information about the experience of people with intellectual disabilities in the medication use process. Six people with intellectual disabilities consented to be interviewed by a pharmacist to determine their knowledge and views of medication use. Data from semi-structured interviews were analysed using a grounded theory approach. Self-determination and risk to the quality of the medication use process were identified as theories. Literature review provided two explanations—vulnerabilities of people with intellectual disabilities in healthcare and pharmacists have a role to play in ensuring a quality medication use process for people with intellectual disabilities. People with intellectual disabilities may be ‘expert patients’ and can provide valuable insights into their experience of medication use. They may be ‘high risk’ patients but may not be recognized as such by pharmacists.
Keywords: intellectual disabilities; Medication use; Pharmacist; Carer; Quality; Information transfer; Medication risk; Experience; Health inequalities; Inclusive Society; ADULT PATIENTS; Ageing and intellectual disability; Autonomy and Disability; CARER; CARER BURDEN; CARERS; CONSULTATION; Clinical Pharmacy; Families & Social Change; Inclusive global health (especially disability and ethnicity; Intellectual Disability; MEDICATION; MEDICATION COMPLIANCE; MEDICATION ERRORS; MEDICATION MANAGEMENT; MEDICATION USE; MEDICATIONS; Medication burden; Medication safety; Non-prescription Medicines; PATIENT EDUCATION; PATIENTS PRIORITIES; PHARMACY PRACTICE; POLYPHARMACY; Patient Care and Education; Patient Compliance; Patient Engagement; Patient experience; Patient experience of services; Patient safety; Pharmacy; Practice of pharmacy; Public Health; Self-Medication; community pharmacy; down syndrome and intellectual disability; health inequalities; medication information; medicines information; mental health and intellectual disability; patient advice; patient information; pharmacist/patient relationship; practice issues, patient education